How Teachers Respond to Pension System Incentives: New Estimates and Policy Applications - Ni, Shawn; Podgursky, Michael (Journal of Labor Economics, 2016)
Rising costs of public employee pension plans have caused fiscal stress in many cities and states and have led to calls for reform. To assess the economic consequences of plan changes, it is important to have reliable statistical models of employee retirement behavior. The authors estimate a structural model of teacher retirement using Missouri administrative panel data. A Stock-Wise option value model provides a good fit to the data and predicts well out-of-sample on the effects of pension enhancements during the 1990s. The structural model is used to simulate the effect of alternatives to the current defined benefit plan.